2005
DOI: 10.1099/jmm.0.46015-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus RNA sequences in sera of schoolchildren in the general population and their association with type 1-diabetes-associated autoantibodies

Abstract: Type 1 diabetes (T1D) is an autoimmune disease linked with genetic factors as well as with environmental triggers, such as virus infections, but the aetiology is still unclear. The authors analysed serum from autoantibody-positive (n ¼ 50) and autoantibody-negative (n ¼ 50) schoolchildren as well as children newly diagnosed with T1D (n ¼ 47; time from diagnosis, median 5 days, interquartile range 1-12 days) for the presence and frequency of enterovirus (EV) and adenovirus sequences. The autoantibody-positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 36 publications
9
30
1
Order By: Relevance
“…vp1 staining in islets was found in~10% of non-diabetic controls of all ages. This is consistent with studies showing that 4-5% of normal children had enteroviral RNA in their serum [4,7,8] and 11.8% had enteroviral RNA present in faecal samples [34,35]. Since a range of enteroviruses can infect human islets in vitro [12,36,37] it is possible that the pancreas is frequently colonised during an enteroviral infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…vp1 staining in islets was found in~10% of non-diabetic controls of all ages. This is consistent with studies showing that 4-5% of normal children had enteroviral RNA in their serum [4,7,8] and 11.8% had enteroviral RNA present in faecal samples [34,35]. Since a range of enteroviruses can infect human islets in vitro [12,36,37] it is possible that the pancreas is frequently colonised during an enteroviral infection.…”
Section: Discussionsupporting
confidence: 89%
“…Much of the evidence is circumstantial [1] but includes observations that antibodies against common Coxsackie B enteroviruses (CVB) and enteroviral RNA occur more frequently in the circulation of recent-onset type 1 diabetes patients than in controls [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results show the association between echovirus epidemics and the induction of T1D associated autoantibodies. Other studies have shown similar results (Frisk & Tuvemo, 2004;Hiltunen et al, 1997;Lonnrot et al, 2000a;Moya-Suri et al, 2005;Oikarinen et al, 2011;Sadeharju et al, 2001;Salminen et al, 2003;Williams et al, 2006). Diabetogeneicity seems to be associated to HEVs of the B species although it is not restricted to one particular serotype or strain.…”
Section: Wwwintechopencomsupporting
confidence: 71%
“…As shown in table 5, subjects at diagnosis and subjects with ICA showed higher frequencies of HEV RNA than their matched controls. These and other results (Andreoletti et al, 1997;Clements et al, 1995;Craig et al, 2003;Moya-Suri et al, 2005;Nairn et al, 1999;Yin et al, 2002) Table 5. Frequency of enterovirus RNA in blood of subjects with T1D at clinical onset, their first degree relatives and controls matched for age, sex, date of collection and location (Sarmiento et al, 2007a).…”
Section: Detection Of Hevs At T1d Onset and In Prediabetic Stagesmentioning
confidence: 99%
“…an epitope common for several enteroviruses, enables to detect antibodies against the majority of existing enterovirus serotypes. 4 Enterovirus infection(s) might be involved in the development of type 1 diabetes, 3,[5][6][7] even though some studies are contradicting. [8][9][10] Our previous epidemiological investigations clearly speak about the existence of inverse association between the prevalence of enterovirus infections and frequency of type 1 diabetes in background population.…”
Section: Enterovirus Infections In Young Infantsmentioning
confidence: 99%